Coronary Obstruction Following Transcatheter Aortic Valve Implantation - Ribeiro, Henrique Barbosa (Sociedade Brasileira de Cardiologia, 2014)
BACKGROUND: Transcatheter aortic valve implantation (TAVI) was established as an important alternative for high-risk patients with severe aortic stenosis. However, there are few data in the literature regarding coronary obstruction, that although rare, is a potentially fatal complication. OBJECTIVE: Evaluate this complication in Brazil. METHODS: We evaluated all patients presenting coronary obstruction from the Brazilian Registry of TAVI. Main baseline and procedural characteristics, management of the complication, and clinical outcomes were collected from all patients. RESULTS: From 418 consecutive TAVI procedures, coronary obstruction occurred in 3 cases (incidence of 0.72%). All patients were women, without prior coronary artery bypass grafting (CABG), and with mean age of 85 ± 3 years, logistic EuroSCORE of 15 ± 6% and STS-PROM score of 9 ± 4%. All of the cases were performed with balloon-expandable Sapien XT prosthesis. In one patient, with pre-procedural computed tomography data, coronary arteries presented a low height and a narrow sinus of Valsalva. All patients presented with clinically significant severe maintained hypotension, immediately after valve implantation, and even though coronary angioplasty with stent implantation was successfully performed in all cases, patients died during hospitalization, being two periprocedurally. CONCLUSION: Coronary obstruction following TAVI is a rare but potentially fatal complication, being more frequent in women and with the balloon-expandable prosthesis. Anatomical factors might be related with its increased occurrence, highlighting the importance of a good pre-procedural evaluation of the patients in order to avoid this severe complication.